BRAZILIAN NEOLIBERAL STATE IN 2019: THE SITUATION OF THE BOLSA FAMÍLIA AND THE ANTI-CRIME PACKAGE - Ribeiro, Luísa Neis; Heinen, Luana Renostro (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The present paper analyzes two policies, in order to identify whether the Brazilian State can be characterized as a Centaur State in the sense proposed by Loïc Wacquant: human, conciliatory and liberator for the dominant classes (with restricted performance in the economic domain, aimed at tax incentives), and, on the other hand, horse - penalizing and restrictive for the lower classes (active to generate unprotected workers and in the prosecution and penal control). Policies aimed at the poorest populations were selected, fundamentally a social policy, the Bolsa Família Program, and an incarceration policy, the Anticrime Package (Law No. 13.964/ 2019). The methodology adopted was the legal-institutional approach for the study to consider its institutional, political and social aspects, but without neglecting its legal conformation. Regarding Bolsa Família, the ministerial reorganization since the Temer government has made social assistance less important, in addition to budget cuts. Finally, the analysis of the Anticrime Package led to the conclusion that there will be an increase in incarceration due to increased penalties, reduced resources in the criminal process and changes to preventive detention and criminal prescription. Although criminal policy cannot be considered a social policy in the strict sense, it is concluded that in the discourse and political practice of the architects of the neoliberal State, the aggrandizement of the punitive apparatus is presented as the answer to public problems that would deserve the institutionalization of policies articulated social issues.